Preoperative transarterial embolization using gelatin sponge for hypervascular bone and soft tissue tumors in the pelvis or extremities. (April 2016) - Shimohira, Masashi; Nagai, Keiichi; Hashizume, Takuya; Nakagawa, Motoo; Ozawa, Yoshiyuki; Sakurai, Keita; Matsushita, Yasushi; Yamada, Satoshi; Otsuka, Takanobu; Shibamoto, Yuta
Background: Preoperative transcatheter arterial embolization for hypervascular bone and soft tissue tumors plays an important role in reducing intraoperative blood loss (IBL). Purpose: To evaluate the use of a gelatin sponge in preoperative transcatheter arterial embolization for hypervascular bone and soft tissue tumors in the pelvis or extremities. Material and Methods: Thirty-seven patients (21 men, 16 women; median age, 61 years; age range, 23–79 years) underwent preoperative transcatheter arterial embolization between April 2004 and January 2015. Medical records and images were reviewed, and the technical success rate, clinical success rate, and complications were evaluated. Technical success was defined as a devascularization rate of 75% or higher, and clinical success was defined as intraoperative blood loss (IBL) <1500 mL in cases undergoing surgery within 3 days of transarterial embolization and <3000 mL in cases operated 4 or more days later. Results: Tumor sizes were in the range of 2.0–13.0 cm (median, 5.0 cm). The devascularization rate was decreased by >75% at follow-up angiography in all cases, and the technical success rate was 100 % (37/37). The median IBL was 491 mL (range, 30–3800 mL), and the clinical success rate was 89% (33/37). The minor complication of local pain was observed in 13 out of 37 cases (35%) during or after embolization, but was controllable by an analgesic. Conclusion: Preoperative transarterial embolization using a gelatin sponge appears to be feasible and safe, and may contribute to decreasing IBL.